Dumping Problems on Business Competition in Tax Law Aspects - Zuki, Ade (Department of Islamic Economic Law, Faculty of Sharia, Sultanah Nahrasiyah State Islamic University, Lhokseumawe, 2024)
The impact of globalization has resulted in many countries becoming increasingly interdependent, prompting many countries to intensify international trade flows through cross-border cooperation. The problems above some of them occur on exports and imports. Manufacturers from different countries need to compete in reality, with an orientation to dominate large-scale markets. The domestic market of a country through a variety of ways. Among the measures taken by a producer of such a country is to lower prices irrationally, or called dumping, to the lowest point than the price in place in the country concerned. The exclusion of the producer affects the marketing price of its similar commodities, thus complicating the production of the country's intended commodity and resulting in a reduction in production. This research uses a literary study or a library survey. Literature studies are research approaches aimed at gathering quality data sources based on a specific topic. The aim of literature studies is to describe the main content based on available information. The results of the study showed that dumping is a mechanism to market a commodity to the country market for a large quantity and to deal with very low nominal (cheap) expects not to lower the purchase price in the country in order to be able to'subjugate' the country's market and can regain price control. There's a variety of influences triggered by dumping practices. Therefore, this article sets out a measure to deal with it, namely the anti-dumping rules.